Strengthening patient safety strategies: an integrative review as to drug safety processes (Research, Society and Development, 2020)
Objectives: To identify evidence regarding the processes used to promote patient safety related to the use of drugs in hospital environments and what implications these actions have for clinical practice and pharmaceutical care. Methods: Integrative review carried out on the databases, Cochrane Library, Epistemonikos, Health Evidence, Health Systems Evidence, and Virtual Health Library, using the domains "elderly", "patient safety", "polypharmacy" combining them with the Boolean operators 'AND' and 'OR'. The publications were selected according to the inclusion and exclusion criteria; the articles were analyzed in pairs; there was no language restriction. Results: The search resulted in 73 articles, of which: 42 were excluded due to different themes to that of this review, 4 systematic reviews, and 3 duplicates. There remained 24 eligible articles divided into 5 thematic axes: perception of professionals and patients regarding safety in the use of medicines; delivery systems and standardized drug list; drug dispensing by pharmacists and pharmacy technicians; stability test; and, quality and management of assistance processes. Conclusion: There are numerous strategies employed to promote safety in the use of medicines and the pharmacist, as a technical and clinical consultant in pharmaceutical care, can act by detecting potential flaws and outlining strategies to promote patient safety in order to reduce costs with health technologies.